Knowledge Management in the Application of Banana Shoot Microorganisms by Shrimp Farmers’ Groups to Address White Feces Syndrome - Katepan, Pimolwan; Yarangwong, Arissara; Wuthipan, Itthiwat; Sittivech, Praseatsak; Kheerajit, Cherdpong; Dokmaithes, Rapee; Thaisom, Rungthip (Journal of Management Science Nakhon Pathom Rajabhat University, 2025)
White Feces Syndrome has been a persistent issue for shrimp farmers, leading to significant losses in both shrimp yield and farmer income. This condition arises from inflammation of the shrimp’s intestine caused by bacterial infections, leading to poor nutrient absorption in the gut. A survey conducted in Sa Si Mum Subdistrict, Kamphaeng Saen District, Nakhon Pathom Province, revealed that most shrimp farmers in the area are affected by this condition. Consequently, the objectives of this study were to 1) examine the general information of shrimp farmers in Sa Si Mum Subdistrict, and 2) to evaluate the knowledge management for the use of banana shoot microorganisms by a group of shrimp farmers to solve the White Feces Disease problem. The study employed qualitative and survey research methods, utilizing in-depth interviews to collect primary data from 20 shrimp farmers who served as key informants, selected through purposive sampling. The data were analyzed using descriptive statistics, including frequency and percentage. The findings indicated that 1) the majority of farmers (60.00%) were male, most (40.00%) were between the ages of 31-40, and 45.00% had completed primary school education. Baseline data are employed in the planning of communication strategies and the design of activities that correspond to the knowledge levels of farmers. 2) Evaluation results of knowledge management on the use of banana shoot microorganisms by shrimp farmers to address the White Feces Disease problem revealed that farmers were able to effectively apply the acquired knowledge, particularly in preventing and mitigating the severity of the disease. By applying banana shoot microorganisms at a rate of 10 liters per rai across 20 shrimp ponds owned by participating farmers, the implementation of this knowledge produced positive outcomes in various aspects of shrimp farming. The use of banana shoot microorganisms led to only a marginal increase in production costs, amounting to just 220 baht per farmer. Article history: Received 3 February 2024 Revised 19 September 2025 Accepted 22 September 2025 SIMILARITY INDEX = 2.26 %